Review of toxicity emission from municipal wastewater treatment by life cycle assessment / Siti Safirah Rashid ... [et al.] - Rashid, Siti Safirah; Yong, Qiang Liu; Mokhtar, Hamizah; Zainudin, Mohd Razmi; Muda, Mohd Fakri (Universiti Teknologi MARA, Pahang, 2022)
Sewage treatment removes contaminants in wastewater, however pollutants from wastewater could also be transmitted to air, water and soil which could lead to negative impacts on the environment. The overall environmental impact from wastewater treatment plants (WWTPs) is very challenging to evaluate because conventional assessment tool such as environmental impact assessment (EIA) did not consider overall processes or input and output of the treatment plant. Therefore, a holistic method such as life cycle assessment (LCA) is needed to analyze the impact of WWTP's operation on the environment. This paper reviews the toxicity impact of WWTPs by LCA. The importance of toxic micropollutants impact from WWTPs will be discussed. Furthermore, studies regarding different life cycle impact assessment (LCIA) methodology used for toxicity impact assessment will be reviewed. Finally, a comparison on toxicity impact studies by LCA in developing countries also will be review. This review found that there is lack of studies concerning life cycle assessment that includes both metals and PPCPs contents in WWTPs especially in developing countries. Thus it is important to investigate higher number of micropollutants and other life cycle toxicity impacts from wastewater treatment plants using different LCIA methods especially in developing countries' situations to provide valuable info for LCA practice.